(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
Unlike other legislative capitula – widely quoted in the documents of the regnum Italiae throughout the early Middle Ages – the extra-edictal tradition of King Liutprand’s Law no. 91 began suddenly and late, shortly after the year 1000, and just as abruptly, at the end of the 11th century, it disappeared from notarial practice. In that period, however, it proved to be a valuable resource at the service of the need to strengthen the firmitas of specific typologies and documentary events, both inside and outside the spaces in which legislation itself and the juridical exegesis had placed it. What were these spaces? To what precise needs for action and documentation was the recovery of a three-hundred-year-old law linked? What were the characteristics of its reuse and its actualisation in the charters of the two areas of the regnum (the Subalpine/Lombard territories and southern Marche) that preserve evidence of it?